Interactive Media Application of Articulate Storyline 3 in Information Services with the Topic of Self-Regulation for Students of SMP Negeri 1 Percut Sei Tuan - Abdul Munir; Rafael Lisinus Ginting; Nur Izharni (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2025)
This study aims to develop interactive media using the Articulate Storyline 3 software in information services for students of SMP Negeri 1 Percut Sei Tuan with a focus on the topic of self-regulation in learning. This type of research is research and development. This study uses a 4-D development model, which consists of 4 main steps, namely: Define, Design, Develop, and Disseminate. Data collection techniques in this development research use interviews, observations and questionnaires. The data analysis technique for this study is in the form of qualitative descriptive data analysis and quantitative descriptive data analysis. The results of the validation test with material expert validation of 3.63, media expert validation of 3.83, field practitioner validation of 3.93 with the overall categorized as "Very Valid" so that it is worthy of use. In the practicality test through the student response sheet, 94% were categorized as "Very Practical". In the effectiveness test through student worksheet, the results were 95% with the category of "Very Effective". Thus, overall it can be concluded that the interactive media Articulate Storyline 3 with the topic of self-regulation in learning developed is valid, practical and effective.